The Effect of Ceramic Substrate Moisture on the Adhesion of Waterproofing Coatings - Kendzierawska, Weronika Anna; Trochonowicz, Maciej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this article is to present issues related to the impact of substrate moisture on the adhesion of various types of waterproofing used on ceramic surfaces. The work focuses on a detailed analysis of the results of bond strength tests, which were carried out at different substrate moisture levels ranging from 0% to 12%. Six different types of waterproofing materials were analyzed in the tests.
Keywords: waterproofing; adhesion; bonding strength; ceramic substrates